Analysis of diversity of hepatitis C virus glycoproteins E1 and E2 - Hudson, Natalia Joanna (2012)
Hepatitis C Virus (HCV) exists as a population of sequence variants that evolves during infection adapting to host pressures. The main targets for the immune response are the envelope glycoproteins E1 and E2, which also mediate viral cell entry. The first hypervariable region (HVR1) of E2, previously implicated in the outcome of acute infection, has been a focus of many studies. However more broadly neutralising antibodies tend to target epitopes outside this region, yet evolution of full length E1E2 heterodimer is poorly understood. The HCV transmission and window period as well as seroconversion are the evolutionary events shaping primary infection hence influencing outcome of acute infection. However, due to the asymptomatic character of the early phases of HCV infection, evolutionary data describing this interval is still lacking depth. Defining the genetic and phenotypic characteristics of HCV population of sequence variants that establish infection in a new host would aid vaccine and new therapy design. This study aimed to identify patterns of HCV envelope glycoprotein evolution upon transmission and during early phases of disease. We studied this in three settings: experimental transmission of immunocompromised mice by known inoculum; occurrence of horizontal transmission in a haemodialysis unit between hypothesised source and index case individuals; and unrelated cases of acutely infected HCV patients. The single genome amplification (SGA) approach was utilised, which allowed us to accurately assign linkage between substitutions and determine the frequency distribution of E1E2 variants in analysed viral populations. Data from the first experimental setting indicates that a selective sweep occurs upon HCV transmission, with selective amplification of envelope sequence variants that possess fitness advantage at entry level. Molecular determinants associated with this enhanced infectivity have also been identified. In further part of the project we confirmed a horizontal infection in haemodialysis unit with use of phylogenetic methods and suggested revision of current safety guidelines. Analysis of sequences from the last setting showed that indeed HVR1 might not be a good enough indicator of evolutionary events in the acute phase, as linked substitutions occur also outside this region. Seroconversion is associated with increasing population diversity indicating role of antibodies in driving HCV evolution, which is host specific.